Design and Application of Highly Responsive Fluorescence Resonance Energy Transfer Biosensors for Detection of Sugar in Living Saccharomyces cerevisiae Cells - Ha, Jae-Seok (American Society for Microbiology (ASM), 2007)
A protein sensor with a highly responsive fluorescence resonance energy transfer (FRET) signal for sensing sugars in living Saccharomyces cerevisiae cells was developed by combinatorial engineering of the domain linker and the binding protein moiety. Although FRET sensors based on microbial binding proteins have previously been created for visualizing various sugars in vivo, such sensors are limited due to a weak signal intensity and a narrow dynamic range. In the present study, the length and composition of the linker moiety of a FRET-based sensor consisting of CFP-linker(1)-maltose-binding protein-linker(2)-YFP were redesigned, which resulted in a 10-fold-higher signal intensity. Molecular modeling of the composite linker moieties, including the connecting peptide and terminal regions of the flanking proteins, suggested that an ordered helical structure was preferable for tighter coupling of the conformational change of the binding proteins to the FRET response. When the binding site residue Trp62 of the maltose-binding protein was diversified by saturation mutagenesis, the Leu mutant exhibited an increased binding constant (82 μM) accompanied by further improvement in the signal intensity. Finally, the maltose sensor with optimized linkers was redesigned to create a sugar sensor with a new specificity and a wide dynamic range. When the optimized maltose sensors were employed as in vivo sensors, highly responsive FRET images were generated from real-time analysis of maltose uptake of Saccharomyces cerevisiae (baker's yeast).